Lipid Profile, Blood Glucose Level and Body Mass Index (BMI) in Second Trimester of Pregnancy: Screening with Gestational Diabetes: Profil Lipid, Gula Darah dan Indeks Massa Tubuh (IMT) pada Kehamilan Trimester II: Skrining Kejadian Kehamilan dengan Diabetes Melitus - Donny S. Winardo; John J. E. Wantania; Suzanna P. Mongan (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To find out lipid profile data, blood sugar and Body Mass Index in trimester II pregnancy to the incidence of pregnancy with diabetes mellitus. Methods: This study is a cross sectional study. The number of samples obtained was 42 samples where all were taken in the second trimester. Samples taken from RSUP Prof. Dr. R. D. Kandou Manado and networking hospitals around Manado that meet the inclusion and exclusion criteria. All patient patients were explained about the research procedure and the signing of consent information. Blood samples were taken for examination of blood sugar (fasting blood sugar and 2 hours post-prandial blood sugar) and lipid profiles (total cholesterol, HDL, LDL, triglycerides). After the data is collected, it is included in the SPSS version 22.0 program for data analysis. Results: Found 2 subjects (4.76%) who had abnormal fasting blood sugar and found 4 subjects (9.53%) who had abnormal 2-prandial 2-hour blood sugar. For lipid profiles, it was found 16 subjects (38.1%) who had abnormal total cholesterol levels, for LDL there were 13 subjects (30.96%) who had abnormal levels, for HDL there were 4 subjects (11.9%) who had abnormal levels and for triglycerides there were 23 subjects (54.76%) who had abnormal levels. There was a significant negative correlation between LDL cholesterol and fasting blood sugar (p = 0.002; r = - 0.455), and so did total cholesterol with fasting blood sugar (p = 0.047; r = - 0.302). There was a significant correlation between BMI and total cholesterol (p = 0.013; r = 0.371). There was 1 subject (2.38%) diagnosed with gestational diabetes melt and fasting blood sugar at 190 mg / dL, for prandial 2 hours post blood sugar at 309 mg / dL and for triglycerides at 617 mg / dL. Conclusions: Based on this study found the incidence of gestational diabetes mellitus 2.38% of all trimester II pregnancies. There is a positive but not significant correlation between blood sugar and triglycerides, whereas there is no significant relationship between blood sugar and other lipid profiles. There is a positive but not significant correlation of BMI in trimester pregnancy with total cholesterol. Keywords: Blood sugar, Body Mass Index (BMI), lipid profile Abstrak Tujuan: Untuk mengetahui data profil lipid, gula darah dan Indeks Massa Tubuh pada kehamilan trimester II terhadap kejadian kehamilan dengan diabetes melitus. Metode: Studi ini merupakan studi potong lintang. Jumlah sampel yang didapatkan sebesar 42 sampel di mana seluruhnya diambil pada trimester II. Sampel diambil dari RSUP Prof. Dr. R. D. Kandou Manado dan rumah sakit jejaring sekitar Manado yang memenuhi kriteria inklusi dan eksklusi. Semua pasien-pasien dijelaskan mengenai prosedur penelitian dan penandatanganan inform consent baru dilakukan pengambilan sampel darah untuk pemeriksaan gula darah (gula darah puasa dan gula darah 2 jam postprandial) dan profil lipid (Kolesterol total, HDL, LDL, Trigliserida). Setelah data dikumpulkan, maka dimasukkan ke dalam program SPSS versi 22.0 untuk data analisis. Hasil: Ditemukan 2 subjek (4,76%) yang memiliki gula darah puasa abnormal dan ditemukan 4 subjek (9.,53%) yang memiliki gula darah 2 jam postprandial yang abnormal. Untuk profil lipid, ditemukan 16 subjek (38,1%) yang memiliki kadar kolesterol total abnormal, untuk LDL ditemukan sebanyak 13 subjek (30,96%) yang memiliki kadar abnormal, untuk HDL ditemukan 4 subjek (11,9%) yang memiliki kadar abnormal dan untuk trigliserida ditemukan 23 subjek (54,76%) yang memiliki kadar abnormal. Terdapat korelasi negatif signifikan antara kolesterol LDL dengan gula darah puasa (p = 0,002 ; r = – 0,455), dan begitu juga dengan kolestrol total terhadap gula darah puasa (p = 0,047 ; r = – 0,302). Terdapat korelasi signifikan antara IMT dengan kolesterol total (p = 0,013 ;r = 0,371). Terdapat 1 subjek (2,38%) yang terdiagnosis diabetes melitus gestasional di mana gula darah puasa sebesar 190 mg/dL, untuk gula darah 2 jam postprandial sebesar 309 mg/dL dan untuk trigliserida sebesar 617 mg/dL. Kesimpulan: Berdasarkan penelitian ini ditemukan kejadian diabetes melitus gestasional 2,38% dari seluruh kehamilan trimester II. Terdapat korelasi positif tetapi tidak bermakna antara gula darah dengan trigliserida, sedangkan tidak terdapat hubungan bermakna antara gula darah dengan profil lipid lainnya. Terdapat korelasi positif tetapi tidak bermakna IMT pada kehamilan trimester dengan kolestrol total. Kata kunci: gula darah, Indeks Massa Tubuh (IMT), profil lipid